Lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material and preparation method thereof

Through the preparation method of lithium oxalate/CNT coated modified lithium-rich manganese positive electrode material, the problem of irreversible oxygen loss and phase change during the circulation process of lithium-rich manganese positive electrode material is solved, and the effect of improving the first effect and circulation performance of the material is achieved.

CN119786583AActive Publication Date: 2025-04-08QINGDAO QIANYUN HIGH TECH NEW MATERIAL
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510030698.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-08
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the first-effect curlon efficiency and circulation performance of lithium-rich manganese positive electrode materials, and there are problems of irreversible oxygen loss and phase change during the circulation process.

Method used

The preparation method of lithium oxalate/CNT coated modified lithium-rich manganese positive electrode material is adopted, and the lithium oxalate and CNT cladding layers are formed through co-precipitation reaction and sintering steps to improve the conductivity and stability of the material.

Benefits of technology

The first Coulomb efficiency and energy density of lithium-rich manganese cathode materials are improved, the cycle stability and rate performance of the material are enhanced, and the problems of lithium ion deintercalation and oxygen release are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786583A_ABST
    Figure CN119786583A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material and a preparation method thereof.The preparation method comprises the steps that S1, a metal salt solution, a precipitator and a complexing agent are introduced into a reaction container in a parallel flow mode, a co-precipitation reaction is conducted, aging, filtering and drying are conducted after the reaction is finished, and a lithium-rich manganese-based positive electrode material precursor is obtained; s2, uniformly mixing the lithium-rich manganese-based positive electrode material precursor and a lithium source, raising the temperature to 800-900 DEG C at the rate of 4-6 DEG C / min, and sintering for 8-16 hours to obtain a lithium-rich manganese-based positive electrode material LMR; s3, oxalic acid dihydrate, CNT and LMR are added into water, heating and uniform stirring are performed, and composite slurry is obtained; s4, dissolving lithium hydroxide in water, dropwise adding into the composite slurry, and continuously stirring to obtain reaction slurry; and S5, filtering and drying the reaction slurry to obtain the lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material. According to the invention, the first coulombic efficiency, the cycle performance and the rate performance of the lithium-manganese-rich positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and particularly relates to a lithium oxalate / CNT-coated modified lithium-rich manganese cathode material and a preparation method thereof. Background Art

[0002] With the continuous development of electronic devices such as spacecrafts, electric vehicles, medical devices, and communication devices, lithium-ion batteries have become an indispensable part thereof; however, their energy density still needs to be further improved to meet the application in new energy vehicles.

[0003] The energy density of a single lithium-ion battery is determined by the working voltage and the battery capacity of the battery itself. Therefore, the battery energy density can be increased by increasing the battery working voltage or capacity. The layered lithium-rich manganese-based cathode material xLi2MnO3·(1-x)LiMO2 (0 < x < 1) is composed of LiMO2 (M = Mn, Co, Ni) and Li2MnO3, and its discharge specific capacity at 2 - 4.8V can reach 250 - 300 mAh / g, and it is considered an ideal cathode material for high-energy density lithium-ion batteries. The lithium-rich manganese-based material has a unique anion redox mechanism. Although this mechanism contributes to a high specific capacity, it also causes instability of the crystal structure of the lithium-rich material, oxygen loss, and transition metal migration, etc., which in turn lead to problems such as voltage and capacity attenuation during the cycling process, a low first-cycle Coulomb efficiency, and poor cycling performance.

[0004] At present, domestic and foreign researchers usually adopt modification methods such as surface modification, bulk doping, and morphology structure to alleviate problems such as irreversible oxygen loss and phase change during the cycling process of lithium-rich manganese-based materials. Among them, surface modification mainly uses substances such as metal oxides, fluorides, graphene, polymers, etc., and there are relatively few reports on using organic cathode lithium replenishing agents. Lithium oxalate (Li2C2O4) is considered to be one of the most promising lithium compensation materials. It can decompose to generate Li + at about 4.7V, providing a capacity of 440 mAh / g, which can make up for the lithium loss of the lithium-rich manganese-based cathode material during the first charge and discharge process, thereby improving its first efficiency and energy density; and compared with other lithium replenishing materials, organic lithium salts have a lower decomposition potential, a simple preparation method, are stable to air and moisture, and the decomposition products are gases, which can be discharged during the battery preparation process. However, the Li2C2O4 material has poor electronic conductivity and a relatively high decomposition potential (4.7V), which limits its further application. Summary of the Invention

[0005] The technical problem to be solved by the present invention is: to overcome the deficiencies of the prior art and provide a lithium oxalate / CNT-coated modified lithium-rich manganese cathode material and a preparation method thereof, which can not only improve the first-cycle Coulomb efficiency of the lithium-rich manganese cathode material, but also improve its cycling and rate performance.

[0006] The technical solution of the present invention is:

[0007] On the one hand, the present invention provides a method for preparing a lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material, comprising the following steps:

[0008] S1: introducing a metal salt solution, a precipitant and a complexing agent into a reaction container in parallel to perform a coprecipitation reaction, and aging, filtering and drying after the reaction to obtain a lithium-rich manganese-based positive electrode material precursor;

[0009] S2: uniformly mixing the lithium-rich manganese-based cathode material precursor and the lithium source, heating to 800-900°C at a rate of 4-6°C / min, and sintering for 8-16h to obtain the lithium-rich manganese-based cathode material LMR;

[0010] S3: adding oxalic acid dihydrate, CNT and LMR into water, heating and stirring to obtain composite slurry;

[0011] S4: dissolving lithium hydroxide in water, adding dropwise to the composite slurry, and continuously stirring to obtain a reaction slurry;

[0012] The S5 reaction slurry is filtered and dried to obtain a lithium oxalate / CNT-coated modified lithium-rich manganese positive electrode material.

[0013] Preferably, in step S1, in the metal salt solution, the metal salts are manganese salts, nickel salts and cobalt salts, the molar ratio of manganese salts, nickel salts and cobalt salts is (5-8):(1-4):(0-2), and the concentration of the metal salt solution is 0.5-4 mol / L; wherein the manganese salt is at least one of manganese sulfate, manganese nitrate, manganese chloride and manganese acetate; the nickel salt is at least one of nickel sulfate, manganese nitrate, nickel chloride and nickel acetate; and the cobalt salt is at least one of cobalt sulfate, cobalt nitrate, cobalt chloride and cobalt acetate.

[0014] Preferably, in step S1, the precipitant is at least one of sodium carbonate solution and sodium hydroxide solution, with a concentration of 0.5-4 mol / L; the complexing agent is at least one of ammonia water, ammonium bicarbonate solution and ammonium carbonate solution, with a concentration of 0.5-2 mol / L.

[0015] Preferably, in step S1, the pH of the coprecipitation reaction is 7-11, the reaction temperature is 50-60° C., and the aging time is 12-24 h.

[0016] Preferably, in step S1, the particle size D50 of the lithium-rich manganese-based positive electrode material precursor is 4-6 μm.

[0017] Preferably, in step S2, the lithium source is at least one of lithium carbonate and lithium hydroxide, and the molar ratio of the lithium source to the lithium-rich manganese-based positive electrode material precursor is (1.2-1.3):1.

[0018] Preferably, in step S3, the mass ratio of the oxalic acid dihydrate to the generated lithium oxalate, CNT and LMR is (1-5):(1-5):100; and the mixture is heated to 50-80°C.

[0019] Preferably, in step S4, the molar ratio of lithium hydroxide to oxalic acid dihydrate is (2-2.05):1; lithium hydroxide is used to control the reaction pH to 7-7.5, and the reaction time is 10-40 min.

[0020] Preferably, in step S5, the drying temperature is 130-160° C., and the drying time is 3-5 hours.

[0021] On the other hand, the present invention provides a lithium oxalate / CNT coated modified lithium manganese rich positive electrode material prepared by the above-mentioned method for preparing the lithium oxalate / CNT coated modified lithium manganese rich positive electrode material.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material prepared by the present invention has a lithium supplementation effect in the lithium oxalate coating layer, which improves the initial coulombic efficiency and energy density of the LMR positive electrode material. At the same time, the CNT coating layer can not only effectively reduce the decomposition voltage of the lithium supplement agent and improve the lithium supplementation efficiency, but also serve as an inert protective layer to protect the LMR positive electrode material, improve the conductivity of the material, reduce the distortion of the material during lithium ion deintercalation, inhibit the release of oxygen and structural phase change, and effectively improve the cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a SEM image of the lithium oxalate / CNT-coated modified lithium-rich manganese positive electrode material prepared in Example 1 of the present invention.

[0025] Figure 2 This is a SEM image of the lithium oxalate / CNT-coated modified lithium-rich manganese positive electrode material prepared in Example 2 of the present invention.

[0026] Figure 3 This is a SEM image of the lithium oxalate / CNT-coated modified lithium-rich manganese positive electrode material prepared in Example 3 of the present invention.

[0027] Figure 4 This is a SEM image of the lithium oxalate / CNT-coated modified lithium-rich manganese positive electrode material prepared in Example 4 of the present invention.

[0028] Figure 5 This is a SEM image of the lithium oxalate / CNT-coated modified lithium-rich manganese positive electrode material prepared in Example 5 of the present invention.

[0029] Figure 6This is a SEM image of the lithium oxalate / CNT-coated modified lithium-rich manganese positive electrode material prepared in Example 6 of the present invention.

[0030] Figure 7 It is a charging dQ / dV curve diagram of the lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material prepared in Example 1 of the present invention and the lithium-rich manganese positive electrode material prepared in Comparative Example 2. DETAILED DESCRIPTION

[0031] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0032] Example 1

[0033] The preparation method of the lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material of this embodiment comprises the following steps:

[0034] S1: weigh manganese sulfate, nickel sulfate and cobalt sulfate according to the molar ratio of Mn, Ni and Co of 6:2:2, dissolve in water to prepare a metal salt solution with a total concentration of 2 mol / L; weigh a certain amount of sodium carbonate to prepare a precipitant with a concentration of 2 mol / L; weigh a certain amount of ammonia water to prepare a complexing agent with a concentration of 1 mol / L; add the three solutions dropwise into the reactor for coprecipitation reaction, control the reaction temperature to 55°C and the pH to 7.8; stop feeding when the particle size of the generated reactant reaches 4-6μm, and after aging reaction for 12h, filter and dry to obtain a lithium-rich manganese-based positive electrode material precursor;

[0035] S2: The lithium-rich manganese-based cathode material precursor and lithium carbonate are uniformly mixed in a molar ratio of 1:1.2, transferred to a muffle furnace, heated to 850°C at a rate of 5°C / min, sintered for 12h, and air was introduced throughout the process. After cooling, the mixture was taken out to obtain Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 material (i.e. LMR);

[0036] S3: According to the mass ratio of lithium oxalate, CNT and LMR generated as 1:5:100, 1.24 g of oxalic acid, 2.5 g of CNT and 50 g of LMR were weighed, added into 500 mL of deionized water, heated to 60°C, and stirred continuously to obtain a composite slurry;

[0037] S4: lithium hydroxide is weighed according to a molar ratio of lithium hydroxide to dihydrate oxalic acid of 2.02:1, and dispersed in 20 mL of deionized water to obtain a lithium hydroxide solution, and the lithium hydroxide solution is slowly added dropwise to the composite slurry, and the final pH is controlled to 7.5 using the lithium hydroxide solution, and the reaction is continuously stirred for 30 minutes to obtain a reaction slurry;

[0038] S5: Filter the reaction slurry and dry it in an oven at 130 °C for 5 h to obtain Li2C2O4 / CNT coated Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 material, denoted as L@C@LMR-1.

[0039] Example 2

[0040] The difference from Example 1 is that in step S3, the mass ratio of the generated lithium oxalate, CNT, and LMR is 2:5:100, and the finally prepared material is recorded as L@C@LMR-2.

[0041] Example 3

[0042] The difference from Example 1 is that in step S3, the mass ratio of the generated lithium oxalate, CNT, and LMR is 3:5:100, and the finally prepared material is recorded as L@C@LMR-3.

[0043] Example 4

[0044] The difference from Example 1 is that in step S3, the mass ratio of the generated lithium oxalate, CNT, and LMR is 4:5:100, and the finally prepared material is recorded as L@C@LMR-4.

[0045] Example 5

[0046] The preparation method of the lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material of this embodiment comprises the following steps:

[0047] S1: weigh manganese sulfate, nickel sulfate and cobalt sulfate according to the molar ratio of Mn, Ni and Co of 6:2:2, dissolve in water to prepare a metal salt solution with a total concentration of 2 mol / L; weigh a certain amount of sodium carbonate to prepare a precipitant with a concentration of 2 mol / L; weigh a certain amount of ammonia water to prepare a complexing agent with a concentration of 1 mol / L; add the three solutions dropwise into the reactor for coprecipitation reaction, control the reaction temperature to 55°C and the pH to 7.8; stop feeding when the particle size of the generated reactant reaches 4-6μm, and after aging reaction for 12h, filter and dry to obtain a lithium-rich manganese-based positive electrode material precursor;

[0048] S2: The lithium-rich manganese-based cathode material precursor and lithium carbonate are uniformly mixed in a molar ratio of 1:1.2, transferred to a muffle furnace, heated to 900°C at a rate of 5°C / min, sintered for 8h, and air was introduced throughout the process. After cooling, the mixture was taken out to obtain Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 material (i.e. LMR);

[0049] S3: According to the mass ratio of lithium oxalate, CNT and LMR generated as 2:4:100, 2.48 g of oxalic acid, 2 g of CNT and 50 g of LMR were weighed, added into 500 mL of deionized water, heated to 60°C, and stirred continuously to obtain a composite slurry;

[0050] S4: lithium hydroxide is weighed according to a molar ratio of lithium hydroxide to dihydrate oxalic acid of 2.02:1, and dispersed in 20 mL of deionized water to obtain a lithium hydroxide solution, and the lithium hydroxide solution is slowly added dropwise to the composite slurry, and the final pH is controlled to 7.2 using the lithium hydroxide solution, and the reaction is continuously stirred for 30 minutes to obtain a reaction slurry;

[0051] S5: Filter the reaction slurry and dry it in an oven at 130 °C for 5 h to obtain Li2C2O4 / CNT coated Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 material, denoted as L@C@LMR-5.

[0052] Example 6

[0053] The preparation method of the lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material of this embodiment comprises the following steps:

[0054] S1: weigh manganese sulfate and nickel sulfate according to the molar ratio of Mn to Ni of 6:2, dissolve in water to prepare a metal salt solution with a total concentration of 2 mol / L; weigh a certain amount of sodium hydroxide to prepare a precipitant with a concentration of 4 mol / L; weigh a certain amount of ammonia water to prepare a complexing agent with a concentration of 1 mol / L; add the three solutions dropwise into the reactor for coprecipitation reaction, introduce nitrogen for protection, control the reaction temperature to 55°C, and the pH to 11; stop feeding when the particle size of the generated reactant reaches 4-6 μm, and after aging reaction for 12 hours, filter and dry to obtain a lithium-rich manganese-based positive electrode material precursor;

[0055] S2: The lithium-rich manganese-based cathode material precursor and lithium carbonate are uniformly mixed in a molar ratio of 1:1.2, transferred to a muffle furnace, heated to 800°C at a rate of 5°C / min, sintered for 16 hours, and air was introduced throughout the process. After cooling, the mixture was taken out to obtain Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 material (i.e. LMR);

[0056] S3: According to the mass ratio of lithium oxalate, CNT and LMR generated as 3:3:100, 3.72 g of oxalic acid, 1.5 g of CNT and 50 g of LMR were weighed, added into 500 mL of deionized water, heated to 60°C, and stirred continuously to obtain a composite slurry;

[0057] S4: lithium hydroxide is weighed according to a molar ratio of lithium hydroxide to dihydrate oxalic acid of 2.02:1, and dispersed in 20 mL of deionized water to obtain a lithium hydroxide solution, and the lithium hydroxide solution is slowly added dropwise to the composite slurry, and the final pH is controlled to 7 using the lithium hydroxide solution, and the reaction is continuously stirred for 30 minutes to obtain a reaction slurry;

[0058] S5: Filter the reaction slurry and dry it in an oven at 130 °C for 5 h to obtain Li2C2O4 / CNT coated Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 material, denoted as L@C@LMR-6.

[0059] SEM images of the lithium oxalate / CNT-coated modified lithium-rich manganese positive electrode material prepared in Example 1-6 are as follows: Figure 1-6 As shown, it can be seen that the prepared lithium oxalate / CNT-coated modified lithium-rich manganese positive electrode material has a uniform particle size distribution and a uniform coating layer on the surface.

[0060] Comparative Example 1

[0061] The difference from Example 1 is that steps S3-S5 are not performed, and Li is finally obtained. 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 material (ie LMR).

[0062] Comparative Example 2

[0063] The difference from Example 1 is that in step S3, no CNT is added, and finally Li2C2O4 coated Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 material, denoted as L@LMR-1.

[0064] Comparative Example 3

[0065] The difference from Example 1 is that in step S3, oxalic acid is not added, and finally CNT-coated Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 material, denoted as C@LMR-1.

[0066] Comparative Example 4

[0067] The difference from Example 1 is that in step S3, according to the mass ratio of lithium oxalate, CNT, and LMR generated being 1:6:100, 1.24 g of oxalic acid, 3 g of CNT, and 50 g of LMR are weighed, added into 500 mL of deionized water, heated to 60°C, and stirred evenly to obtain a composite slurry. Finally, Li2C2O4 / CNT coated Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 material.

[0068] Comparative Example 5

[0069] The difference from Example 1 is that in step S4, a lithium hydroxide solution is used to control the final pH to 8.

[0070] The electrochemical performance tests were performed on the positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-5:

[0071] The positive electrode material, acetylene black and polyvinylidene fluoride (PVDF) binder were mixed uniformly in a mass ratio of 94:3:3, and then dispersed in N-methylpyrrolidone (NMP) solution to obtain a paste-like mixture. The mixture was coated on aluminum foil and vacuum dried at 90°C overnight. Li / Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The assembly of O2 button cells (2016 model) was carried out in a glove box filled with high-purity argon.

[0072] The lithium metal sheet was used as the negative electrode, the polypropylene film was used as the separator, and 1 mol of LiPF6 was dissolved in ethyl carbonate / dimethyl carbonate (EC / DMC, volume ratio 1:1) as the electrolyte. 1.2 Ni 0.13 Co 0.13 Mn 0.54 The pole piece of O2 material is used as the positive electrode material of the battery. The charging and discharging performance test of the lithium-ion battery is carried out on the Blue Electric test system at room temperature, and the test voltage range is 2-4.8V.

[0073] The electrochemical performance test results of the positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-5 are shown in Table 1:

[0074] Table 1 Electrochemical performance test results of positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-5

[0075]

[0076] It can be seen from Examples 1-4 and Comparative Example 1 that with the increase in the amount of lithium oxalate / CNT coating, the discharge capacity, the first coulomb efficiency and the cycle capacity retention rate all increase. This is because the coating provides an additional lithium source during the charge and discharge process, which not only offsets the irreversible lithium loss, reduces the problem of irreversible deposition of lithium metal, but also protects the LMR positive electrode material as an inert protective layer, improves the conductivity of the material, reduces the distortion of the material during lithium ion deintercalation, inhibits the release of oxygen and structural phase change, and ultimately improves the charge and discharge efficiency, energy density and cycle life of the material. It can be seen from Example 1 and Comparative Example 2 that Comparative Example 2 is not coated with CNT, and the discharge capacity and first coulomb efficiency of the positive electrode material are both reduced, but the cycle capacity retention rate decreases most significantly, indicating that the addition of CNT helps to improve the lithium replenishment efficiency of the lithium oxalate lithium replenisher and enhance the stability of the material. It can be seen from Example 1 and Comparative Example 3 that the addition of lithium oxalate lithium replenisher helps to improve the discharge capacity and the first coulomb efficiency. In addition, the charging dQ / dV curves of the lithium oxalate / CNT-coated modified lithium-rich manganese positive electrode material prepared in Example 1 and the lithium-rich manganese positive electrode material prepared in Comparative Example 2 are as follows: Figure 7 As shown by Figure 7 It can be seen that the clear characteristic peak appearing near 4.21V in Example 1 indicates that an obvious electrochemical reaction occurs there, while no obvious characteristic peak appears at 4-4.4V in Comparative Example 2, indicating that no chemical reaction occurs within this voltage range; this indicates that the addition of CNTs can reduce the decomposition voltage of the lithium supplement to about 4.2V.

Claims

1. A method for preparing a lithium oxalate / CNT-coated modified lithium-rich manganese positive electrode material, characterized in that: The following steps are involved: S1: introducing a metal salt solution, a precipitant and a complexing agent into a reaction container in parallel to perform a coprecipitation reaction, and aging, filtering and drying after the reaction to obtain a lithium-rich manganese-based positive electrode material precursor; S2: uniformly mixing the lithium-rich manganese-based cathode material precursor and the lithium source, heating to 800-900°C at a rate of 4-6°C / min, and sintering for 8-16h to obtain the lithium-rich manganese-based cathode material LMR; S3: adding oxalic acid dihydrate, CNT and LMR into water, heating and stirring to obtain composite slurry; S4: dissolving lithium hydroxide in water, adding dropwise to the composite slurry, and continuously stirring to obtain a reaction slurry; The S5 reaction slurry is filtered and dried to obtain a lithium oxalate / CNT-coated modified lithium-rich manganese positive electrode material.

2. The method for preparing the lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material according to claim 1, characterized in that: In step S1, in the metal salt solution, the metal salts are manganese salts, nickel salts and cobalt salts, the molar ratio of manganese salts, nickel salts and cobalt salts is (5-8):(1-4):(0-2), and the concentration of the metal salt solution is 0.5-4 mol / L; wherein the manganese salt is at least one of manganese sulfate, manganese nitrate, manganese chloride and manganese acetate; the nickel salt is at least one of nickel sulfate, manganese nitrate, nickel chloride and nickel acetate; and the cobalt salt is at least one of cobalt sulfate, cobalt nitrate, cobalt chloride and cobalt acetate.

3. The method for preparing the lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material according to claim 1, characterized in that: In step S1, the precipitant is at least one of sodium carbonate solution and sodium hydroxide solution, and the concentration is 0.5-4 mol / L; the complexing agent is at least one of ammonia water, ammonium bicarbonate solution and ammonium carbonate solution, and the concentration is 0.5-2 mol / L.

4. The method for preparing the lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material according to claim 1, characterized in that: In step S1, the pH of the coprecipitation reaction is 7-11, the reaction temperature is 50-60° C., and the aging time is 12-24 hours.

5. The method for preparing the lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material according to claim 1, characterized in that: In step S1, the particle size D50 of the lithium-rich manganese-based positive electrode material precursor is 4-6 μm.

6. The method for preparing the lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material according to claim 1, characterized in that: In step S2, the lithium source is at least one of lithium carbonate and lithium hydroxide, and the molar ratio of the lithium source to the lithium-rich manganese-based positive electrode material precursor is (1.2-1.3):

1.

7. The method for preparing the lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material according to claim 1, characterized in that: In step S3, the mass ratio of the oxalic acid dihydrate to the generated lithium oxalate, CNT and LMR is (1-5):(1-5):100; and the mixture is heated to 50-80°C.

8. The method for preparing the lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material according to claim 1, characterized in that: In step S4, the molar ratio of lithium hydroxide to oxalic acid dihydrate is (2-2.05):1; lithium hydroxide is used to control the reaction pH to 7-7.5, and the reaction time is 10-40 min.

9. The method for preparing the lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material according to claim 1, characterized in that: In step S5, the drying temperature is 130-160° C. and the drying time is 3-5 hours.

10. The lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material prepared by the method for preparing the lithium oxalate / CNT coated modified lithium-rich manganese positive electrode material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lithium-rich anode material for lithium ion battery and preparation method thereof

    CN106328908A

  • Modified lithium iron phosphate composite material, positive electrode material and preparation method thereof

    CN113097455A

  • Monocrystal lithium-rich manganese-based positive electrode material, preparation method thereof and lithium ion battery

    CN118099409A

  • Positive electrode material and preparation method and application thereof

    CN118231606A

  • Composite lithium supplement agent as well as preparation method and application thereof

    CN118507701A